Using Artificial Intelligence (AI) to Boost High School Students' Interest in Learning: A Community Service Project - Diantoro, Karno; Arainy, Corizon Sinar; Soderi, Ahmad; Juwari; Sakti, Essy Malays Sari (Civitas : Jurnal Pengabdian Masyarakat, 2024)
The advancement of artificial intelligence (AI) technology creates new educational opportunities. The purpose of this community service project is to use AI to boost secondary school students' interest in learning. AI-based tools are integrated into the learning process and a series of workshops are used to carry out the program. Among the techniques employed are AI tutoring systems, interactive learning materials, and teacher training. The quality of assignments, length of learning focus, and class participation all significantly rose as a result of the results, indicating a considerable improvement in students' enthusiasm for learning. According to post-program surveys, 90% of teachers believe AI is effective at increasing student engagement, and 85% of students feel that they are more interested in their classes. The infrastructure of technology and the initial adjustment to the new system present the biggest obstacles. To sum up, incorporating AI into education offers a lot of promise to boost student interest in studying, but doing so calls for a planned strategy and continuous assistance.